2009
DOI: 10.1111/j.1545-5300.2009.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Variability in the Manifestation of Expressed Emotion

Abstract: We examined the distribution of expressed emotion (EE) and its indices in a sample of 224 family caregivers of individuals with schizophrenia pooled from 5 studies, 3 reflecting a contemporary sample of Mexican Americans (MA 2000, N ¼ 126), 1 of an earlier study of Mexican Americans (MA 1980, N ¼ 44), and the other of an earlier study of Anglo Americans (AA, N ¼ 54). Chi-square and path analyses revealed no significant differences between the 2 MA samples in rates of high EE, critical comments, hostility, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
(32 reference statements)
0
39
1
3
Order By: Relevance
“…Cross-cultural expressed emotion (EE) research in European American and Mexican American families suggests that when families are hostile and critical (high EE), the symptoms of their family member with schizophrenia increase and they experience higher rates of rehospitalization [35]. Anglo American families in the United States in which recovery outcomes from schizophrenia are less frequent seem to be typically more hostile and critical (high EE) [36].…”
Section: Families and Stigma As Riskmentioning
confidence: 99%
“…Cross-cultural expressed emotion (EE) research in European American and Mexican American families suggests that when families are hostile and critical (high EE), the symptoms of their family member with schizophrenia increase and they experience higher rates of rehospitalization [35]. Anglo American families in the United States in which recovery outcomes from schizophrenia are less frequent seem to be typically more hostile and critical (high EE) [36].…”
Section: Families and Stigma As Riskmentioning
confidence: 99%
“…CFI studies have demonstrated that hostility is rarely seen in the absence of high-EE based on criticism. Thus, researchers using the CFI often combine these categories (e.g., Weisman et al, 1998, 2000; Lopez et al, 2009) and newer systems of rating EE, such as the Five Minute Speech Sample (FMSS; Magaña et al, 1986), do not measure hostility as a separate component; instead, it is combined with criticism. EE is important because it is a robust predictor of illness prognosis across a broad range of psychiatric disorders (Wearden et al, 2000) and, with a few exceptions, across a range of cultures and ethnic groups (Weisman de Mamani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, research on communication in different racial and ethnic groups has shown some differences between non-Hispanic whites and other diverse groups. While expressed emotion, or expressions of over-involvement (“smothering”), criticism or hostility vary from individual to individual; these expressions also vary cross-culturally (41). Moreover, the phenomenon of familial expressed emotion predicts different outcomes depending on the ethnicity of individuals; higher expressed emotion has been linked with poorer outcomes in non-Hispanic whites but not in Hispanic individuals in schizophrenia treatment (4243).…”
Section: Discussionmentioning
confidence: 99%